Kualitas Pelayanan Pengguna Jasa Kereta Api Dalam Transportasi Antarmoda Di Stasiun Gambir - Gusleni, Yessi (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
TI1is research /ms the purpose to know the perceptio11s, e:rpectations, rznd the effecti7.1eness of thequalihj of intemwde transport seruice i11 Gnlllhir stations prm 1irfed hi; PT. Keretn Api (Persero) rzndthe local government of DKJ fnkartn.TI1is research will be done by through a survey methods. Number of samples has been taken atrandom study from a 100 respondents simple. Attribute of the observation are as many as 27attributers of sennce-related to infrastructure, network infrnstructure, operational, and human resources.Resenrclz data in tile descripti7.:ie nnnlysis nnd the senrice qunli ; measuring metlwds includethe reliability, responsir!fness, nssumnce, emplmty, and tangible.From 2 7 nttributes that /un ,e rz lziglz expected mlu.e is the ense of obtaining information routes/busroutes for mil senrice users in intemwde of transport, officers ready to help the train seroi.ces userintermodes of transport, security guamnteess for milway seruice user in intermodes of transport, staffpromde services to train users wlw have limited (disabled, elderly, etc), and security officers, while thepassengers w/w do not satisfi; the sennce quality attnbutes is the ease of obtaining information routes/bus routes for rail seniice users intemwde of trnnsport, sernrity guarantees for milwm; sennce usersin the intemzode of transport, officers prouide sen1ices to train sen1ice users who /un 1e limited (disables,elderly, etc), nnd transport of goods (trolly). Tiie le7.iel of total rnstomer satisfaction is 65,51 %means that the variable qualihj of senrice can not offer the satisfaction of being on the range index ofpoor (64%lebihkecilXd